2018
DOI: 10.1007/s10826-018-1051-2
|View full text |Cite
|
Sign up to set email alerts
|

School Competence among Adolescents in Low-Income Families: Does Parenting Style Matter?

Abstract: In the present study, we investigated parenting styles and self-perceived school competence among low-income adolescents in Norway. The purpose of the study was threefold: 1) to identify differences, if any, in self-perceived school competence between low-income ethnic Norwegians and low-income ethnic minorities; 2) to determine differences, if any, in the perception of parenting styles between the groups; and 3) to determine if parenting styles predict self-perceived school competence in the two groups. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…This suggests that parents who are characterized by an authoritative parenting style are less likely to resist their children's use of smartphones in learning. Our findings reinforce previous studies in the field, which were not related to technology-enhanced learning, that have found that parenting styles in general, and the authoritative parenting style in particular, are powerful predictors of children's well-being in social, psychological and academic realms (Johnsen et al, 2018;Turner, Chandler & Heffer, 2009;Warren et al, 2018). Authoritative parents tend to give their consent to the use of smartphones in learning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that parents who are characterized by an authoritative parenting style are less likely to resist their children's use of smartphones in learning. Our findings reinforce previous studies in the field, which were not related to technology-enhanced learning, that have found that parenting styles in general, and the authoritative parenting style in particular, are powerful predictors of children's well-being in social, psychological and academic realms (Johnsen et al, 2018;Turner, Chandler & Heffer, 2009;Warren et al, 2018). Authoritative parents tend to give their consent to the use of smartphones in learning.…”
Section: Discussionsupporting
confidence: 91%
“…Another parenting style, added later by Maccoby and Martin (1982), is the uninvolved style. The parenting styles typology has been found in many studies as a predictor of the child's welfare in the social, scholastic, behavioral and psychosocial spheres (Baumrind, 1991;Johnsen, Bjørknes, Iversen., & Sandbaek, 2018;Miller et al, 1993, Querido, Warner & Eyberg, 2002Weiss & Schwarz, 1996). Moreover, recent studies have demonstrated the impact of parenting styles on parents' reactions to their children's use of smartphones (Hwang et al, 2017;Jang & Ryu, 2016):…”
Section: Parenting Style and Children's Use Of Smartphonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Norway, support, monitoring and neglect have no significant difference between 253 adolescents 12-18 years of age in their perception of parenting styles 18 .…”
Section: Related Studiesmentioning
confidence: 96%
“…As for family factors, parental behaviors such as help with organizing study and positive reinforcement are predictive of academic self-efficacy (e.g., González-Pienda et al, 2003). Behaviors less closely linked to studying—such as general support, monitoring, or negligence—are also related to students’ self-efficacy (Johnsen et al, 2018; Simpkins et al, 2020). Students’ general mood is also predicted by parents’ behaviors and attitudes.…”
Section: Family and School Determinants Of Self-efficacy And Emotionsmentioning
confidence: 99%